Typification of the names Euphorbia berteroana and Euphorbia bicephala (Euphorbiaceae) - Mugnai, Michele; Lazzaro, Lorenzo; Foggi, Bruno; Guglielmone, Laura; Viciani, Daniele; Ferretti, Giulio (Phytotaxa, 2020)
Euphorbia subsection Hypericifoliae (Euphorbiaceae, Malpighiales) comprises 365 species distributed nearly worldwide and includes E. berteroana, a species widespread in Central and South America and mistakenly reported for Italy. This species was described for the first time by Sprengel based on material collected by Bertero. In the present work we provide a discussion of the main typification issues and the typification of the name E. berteroana and its synonym E. bicephala.